TXD325 : Textile illustration / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This syllabus is designed for textile students to know the basic of the diversity of elements involving textile field such as in interior, fashion and accessory . This subject also for student to learn how to illustrate and understand the different type of textile illustration using various media and techniques based on textile field. Students are given the freedom in producing product sketches that correspond to the design of textile design. Students are required to brainstorm and sketch their ideas individually. They will also get involved with a lot of studio activities and also have to discover, discuss and practice the techniques and styles of drawing based on elements involving textile field such as interior and fashion. At the end of this subject, their final project will be presented/ submit in a critique session.